Workshop on the Implementation of Technology-Based Learning Media - Rahadian, Dian; Hamdani, Hanhan; Basyori, Sansan Ihsan (Fakultas Kewirausahaan Universitas Garut, 2023)
The development of information technology has had a significant impact on the world of education, particularly in the development of technology-based learning media. This Community Service Program (PkM) aims to improve teachers' competence in implementing technology-based learning media through interactive workshops. The activities were carried out in the form of training and hands-on practice in creating digital media relevant to learning needs. The methods used included preparation, implementation, and evaluation of training results. The results of the activity show an increase in teachers' skills in utilizing technology platforms such as interactive learning applications and e-learning. Before the training, the level of teachers' comfort in using technology was only 45%, while after the training it increased to 65%. In addition, participants showed high enthusiasm and were able to produce creative and applicable technology-based learning media. These findings emphasize the importance of continuous training to ensure that teachers are able to integrate technology into the learning process effectively.